Correlation Inquiry between Structure Knowledge and Paragraphs Writing Performance - Samsul Amri (J-SHMIC : Journal of English for Academic, 2016)
This paper aims at investigating the correlative aspect between two variables; structure knowledge and writing performance. It comes up in analyzing the theories and results of some studies that structure knowledge would or would not emphasize in writing performance. It indicates that this phenomenon is being still debated now on. On the sake of this purpose, the research methodology used is correlation design, where it took all the second semester students English Study Program of FKIP- Islamic University of Indragiri as sample. In collecting data, there are two kinds of instrumentation tests; structure knowledge and writing performance tests. While analyzing the data, the researcher used Pearson Product Moment correlation statistical analysis. The finding of the study reveals that there is a positive correlation between the students’ structure knowledge and their writing performance. It is obviously proven that the coefficient correlation is 0.84, which is categorized as high correlation. After testing the hypothesis, the researcher could determine that there is a significant correlation between two variables, since the critical value of rxy is greater than the critical value of rtable in significant level 5%; (rxy = 0.84 > rtable = 0.227). It emphasizes that null hypothesis is rejected and alternative hypothesis is accepted. It infers that who want to have better writing performance should learn structure.